SURGICAL STIMULATORS: History and Perspectives - Tashkenbaeva, U.A.; Okhunov, A.O.; Atakov, S.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
A surgery simulator is computer technology developed to simulate surgical procedures for the purpose of training medical professionals, without the need of a patient, cadaver, or animal. The concept goes back to the 1980s with video games, but only in the 1990s with three-dimensional graphics and the 2000s with the use of motion sensors for realistic movements (motion control) has the technology been able to simulate the real situation. The most common type of surgery taught through this method is laparoscopic surgery, although it has also been used to do a trial run before other kinds of procedures. Cataract surgery and other ophthalmic procedures are also widely taught using surgical simulators.